Safety and Efficacy of Intermittent Colonic Exoperistalsis Device to Treat Chronic Constipation: A Prospective Multicentric Clinical Trial. Issue 12 (16th December 2020) - McClurg, Doreen; Booth, Lorna; Herrero-Fresneda, Immaculada
Abstract : INTRODUCTION: Chronic constipation is associated with various comorbidities and reduced quality of life. Current solutions, either pharmacological or invasive, show limited efficacy. Manual colon-specific massage is a well-established intervention to treat chronic constipation, but it should be applied daily. MOWOOT automatically provides intermittent colonic exo-peristalsis (ICE) treatment like that in manual massage. METHODS: This study assessed the safety and effectiveness of the ICE device to treat chronic constipation due to neurogenic bowel dysfunction or idiopathic causes with high component of pelvic floor disorders. The ICE device was used daily for 20 minutes over 4 weeks. Each participant was followed for 9 consecutive weeks. The same outcome measures (primary: complete bowel movements per week; secondary: Knowles Eccersley Scott Symptom Score and Patient Assessment of Constipation Quality of Life among others) were assessed at baseline (V1), last intervention weeks (V2), and post-treatment (V3). Responders were defined for selected outcomes as better results at V2 respect to V1. RESULTS: N = 92 adult patients constituted the intention-to-treat population, with N = 65 as the per protocol population. Adherence (quantity of treatment received) was ≥95% in the intention-to-treat population. Adverse events related with the treatment were low (8.7%). Using the device significantly increased the number of complete bowel movements per week (V2 − V1 = 1.8 [2.7], P < 0.0001), reduced the symptoms of chronic constipation (Knowles Eccersley Scott Symptom Score V2 − V1 = −3.9 [5.0], P < 0.0001), improved quality of life (Patient Assessment of Constipation Quality of Life V2 − V1 = −0.7 [0.8], P < 0.0001), and facilitated a reduction in laxatives. Colon transit and fecal consistency were not modified. There was a high number of responders (>70%). DISCUSSION: Considering safety, adherence, and efficacy being demonstrated, the results favor the use of MOWOOT to treat chronic constipation (Visual abstract, Supplementary Digital Content 1, http://links.lww.com/CTG/A440 ).